2004
DOI: 10.1111/j.1439-0310.2004.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Incubation Behaviour in Northern Lapwings: Nocturnal Nest Attentiveness and Possible Importance of Individual Breeding Quality

Abstract: Previous studies of sex roles in the polygynous Northern Lapwing Vanellus vanellus have shown that males incubate less than females, perhaps suggesting that sexual selection is important in shaping the parental behaviour of this species. The purpose of this study was to (1) examine for the first time the possibility that males compensate for low diurnal nest attentiveness by increasing their nocturnal assistance and (2) evaluate the hypotheses that sexual selection and individual breeding quality determines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Because female northern lapwings incubate more than males, their energetics should be more affected by an enlarged clutch size than males’. The variance in the sexes’ nest attentiveness is large, though (Lislevand et al . 2003), and larger sample sizes than we have available here might be needed to detect changes in incubation behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because female northern lapwings incubate more than males, their energetics should be more affected by an enlarged clutch size than males’. The variance in the sexes’ nest attentiveness is large, though (Lislevand et al . 2003), and larger sample sizes than we have available here might be needed to detect changes in incubation behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported five eggs in up to 1% of lapwing nests (Cramp & Simmons 1983), but of totally 450 clutches from south‐west Norway 1991–2002, none contained more than four eggs (own unpublished data). Females incubate more than males (during daytime on average about 65% of the time compared to 20% in males), and at night they incubate alone (Parish & Coulson 1998; Liker & Székely 1999; Lislevand et al . in press).…”
Section: Methodsmentioning
confidence: 99%
“…Second, sharing paternal effort with another female could potentially be a problem. In lapwings, males primarily contribute to parental care by taking part in incubation (about 15% on a diurnal basis; Lislevand et al 2004) and by chasing predators, whereas brooding and leading chicks to foraging areas are almost exclusively female tasks (Liker and Székely 1999, Shrubb 2007). To our knowledge, it is not known if polygynous male lapwings provide differential care to their broods after hatching but, if anything, they tend to favour secondary rather than primary clutches during incubation (Grønstøl 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used continuous video-monitoring to describe incubation rhythms of the Northern Lapwing Vanellus vanellus, a common Palearctic shorebird with variable male contribution to incubation (Liker & Szekely 1999; Grønstøl 2003; Jongbloed et al 2006). Current knowledge about incubation of Northern Lapwings is mostly based on brief sampling periods of a few hours (Liker & Szekely 1999; Grønstøl 2003; Lislevand et al 2004; Lislevand & Byrkjedal 2004; but see Jongbloed et al 2006). Subsequently, we know little about the daily and seasonal variation in how sexes divide their incubation duties between and within pairs.…”
Section: Introductionmentioning
confidence: 99%